On Hausdorff-Young inequalities for quantum Fourier transformations - Hudson, R.L. (Український математичний журнал, 1997)
The classical Hausdorff-Young inequality for the Fourier transformation is generalized to various quantum contexts involving noncommutative L p -spaces based on translation-invariant traces. Класична нерівність Хаусдорфа-Юнга для перетворення Фур'є узагальнюється в багатьох квантових контекстах, що включають некомутативні L p -простори, засновані на інваріантних відносно зсуву слідах.